2018
DOI: 10.1039/c8ra02722f
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor miR-449a inhibits the development of gastric cancerviadown-regulation of SGPL1

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that are known to participate in the regulation of many physiological and pathological processes, which can indirectly influence the development of malignant behaviors. Numerous studies have demonstrated that miR-449a plays important roles in human carcinogenesis. However, its precise functional and regulatory roles remain unclear. In this study, we mainly explored the functional role of miR-449a in gastric cancer (GC). The expression levels of miR-449a in 98 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 9 , 10 More importantly, previous studies have demonstrated that miRNAs acting as tumor promoters or anti-oncogenes are involved in the regulation of various tumors. 11 , 12 Recently, growing researches highlighted the importance of miRNAs as a potential diagnostic and prognostic biomarker for cancers, including CC. Several functional miRNAs, such as, miRNA-196a, miRNA-214 and miRNA-92a, have been identified.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 More importantly, previous studies have demonstrated that miRNAs acting as tumor promoters or anti-oncogenes are involved in the regulation of various tumors. 11 , 12 Recently, growing researches highlighted the importance of miRNAs as a potential diagnostic and prognostic biomarker for cancers, including CC. Several functional miRNAs, such as, miRNA-196a, miRNA-214 and miRNA-92a, have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The development of GC involves not only gene mutation but also changes in intracellular signaling pathways 37,38. It has been found that excessive activation of the Akt/m TOR pathway can promote the proliferation and metastasis of tumor cells 39.…”
Section: Discussionmentioning
confidence: 99%